1977
DOI: 10.5962/bhl.title.47454
|View full text |Cite
|
Sign up to set email alerts
|

Beach erosion and accretion at Virginia Beach, Virginia and vicinity / by Victor Goldsmith, Susan C. Sturm, and George R. Thomas ; prepared for U.S. Army, Corps of Engineers, Coastal Engineering Research Center.

Abstract: This report is published to provide coastal engineers with a description of beach erosion and accretion at Virginia Beach, Virginia, including the effect of continuing beach replenishment, and the apparent unimportance of land use in determining erosion. This report also provides benchmark data on coastal processes at the shore north of the CERC Field Research Facility at Duck, North Carolina. The work was carried out under the beach evaluation program of the U.S. Army Coastal Engineering Research Center CCERC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…From this it is concluded that the temperatures were in the range 600-670 ~ C at regional pressures of 5.7 kb (when stratigraphic thickness is taken into consideration). A similar temperature value is also obtained when the development of diopside (Winkler 1976) and scapolite (Goldsmith and Newton 1977) is taken into consideration.…”
Section: P-t Conditionssupporting
confidence: 66%
“…From this it is concluded that the temperatures were in the range 600-670 ~ C at regional pressures of 5.7 kb (when stratigraphic thickness is taken into consideration). A similar temperature value is also obtained when the development of diopside (Winkler 1976) and scapolite (Goldsmith and Newton 1977) is taken into consideration.…”
Section: P-t Conditionssupporting
confidence: 66%